Craniometry of indigenous pigs (Sus scrofa) of north-east India - SARMA, KAMAL; SARMA, M; GOSWAMI, R N; DEVI, J; SARMA, P (The Indian Journal of Animal Sciences, 2014)
The biometry on 5 skulls of indigenous pigs of north-eastern region. popularly known as dum pig. was studicd. The average biometrical measurements of cranial, facial, orbital and mandibular parameters of skull were obtained. Correlation and regression of skull length and skull width with some important parameters wcre also studied, Skull length showed strong positive association with cephalic index, skull base length, cranial length and orbital depth.